2021
DOI: 10.1111/cas.14913
|View full text |Cite
|
Sign up to set email alerts
|

LINC01123 enhances osteosarcoma cell growth by activating the Hedgehog pathway via the miR‐516b‐5p/Gli1 axis

Abstract: Osteosarcoma (OS) is a common malignant bone tumor that is mainly found in the limbs, but can also appear in the axial skeleton. 1 OS occurs primarily in children and adolescents 15-25 years of age. 2 OS has high malignancy, and the main treatment is surgery combined with neoadjuvant radiotherapy and chemotherapy. 3 However, the 5 year survival rate has not substantially improved in the past few decades. Consequently, a greater understanding of the underlying molecular mechanism is needed to provide more effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…LncRNA LINC-PINT, as a tumor suppressor gene, targets miR-425-5p which targets Ptch1 of the Hh pathway to modulate laryngeal carcinoma cell stemness and chemoresistance. Several other regulatory networks comprising lncRNA, miRNA, and mRNA have been reported in the Hh-mediated cancer, including DIO3OS/miR-328/Hhip [ 139 ], GAS5/miR-378a-5p/Sufu [ 140 ], LIFR-AS1/miR-197-3p/Sufu [ 141 ], LOC101930370/miR-1471/Shh [ 142 ], TUG1/miR-132/Shh [ 143 ], LINC01510/miR-335/Shh [ 144 ], LINC01123/miR-516b-5p/Gli1 [ 145 ], NEAT1/miR-503/Smo [ 146 ] and MIRLET7BHG/miR-330-5p/Smo [ 147 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNA LINC-PINT, as a tumor suppressor gene, targets miR-425-5p which targets Ptch1 of the Hh pathway to modulate laryngeal carcinoma cell stemness and chemoresistance. Several other regulatory networks comprising lncRNA, miRNA, and mRNA have been reported in the Hh-mediated cancer, including DIO3OS/miR-328/Hhip [ 139 ], GAS5/miR-378a-5p/Sufu [ 140 ], LIFR-AS1/miR-197-3p/Sufu [ 141 ], LOC101930370/miR-1471/Shh [ 142 ], TUG1/miR-132/Shh [ 143 ], LINC01510/miR-335/Shh [ 144 ], LINC01123/miR-516b-5p/Gli1 [ 145 ], NEAT1/miR-503/Smo [ 146 ] and MIRLET7BHG/miR-330-5p/Smo [ 147 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA HOTAIR overexpression is linked to worse prognosis in patients with renal cell carcinoma [ 153 ]. In osteosarcoma, elevated levels of LINC01123 expression are related with advanced pathological staging [ 145 ]. .Remarkably, miR-324-3p expression is inversely connected with nasopharyngeal carcinoma metastasis but favorably correlated with survival time [ 111 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its abnormal expression is closely related to the occurrence and metastasis of tumors (Kornfeld and Bruning, 2014;Bartonicek et al, 2016). It has been confirmed that multiple lncRNAs can promote the occurrence and metastasis of osteosarcoma through competitive inhibition of miRNA expression (Pan et al, 2021;Zhou and Mu, 2021). Notably, lncRNAs can regulate the development and activation of a variety of immune cells (Atianand et al, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…Recent researches had connected aberrant expression of lncRNAs with the development and progress of osteosarcoma. For example, the upregulated lncRNA LINC01123 in osteosarcoma functioned as a competing endogenous RNA via sponging miR-516b-5p, resulting in accelerated cell progression (Pan et al, 2021). Besides, lncRNAs could also act as prognostic biomarkers.…”
Section: Introductionmentioning
confidence: 99%